Megalin-Mediated Specific Uptake of Chitosan/siRNA Nanoparticles in Mouse Kidney Proximal Tubule Epithelial Cells Enables AQP1 Gene Silencing - Gao, Shan (Ivyspring International Publisher, 2014)
RNAi-based strategies provide a great therapeutic potential for treatment of various human diseases including kidney disorders, but face the challenge of in vivo delivery and specific targeting. The chitosan delivery system has previously been shown to target siRNA specifically to the kidneys in mice when administered intravenously. Here we confirm by 2D and 3D bioimaging that chitosan formulated siRNA is retained in the kidney for more than 48 hours where it accumulates in proximal tubule epithelial cells (PTECs), a process that was strongly dependent on the molecular weight of chitosan. Chitosan/siRNA nanoparticles, administered to chimeric mice with conditional knockout of the megalin gene, distributed almost exclusively in cells that expressed megalin, implying that the chitosan/siRNA particle uptake was mediated by a megalin-dependent endocytotic pathway. Knockdown of the water channel aquaporin 1 (AQP1) by up to 50% in PTECs was achieved utilizing the systemic i.v. delivery of chitosan/AQP1 siRNA in mice. In conclusion, specific targeting PTECs with the chitosan nanoparticle system may prove to be a useful strategy for knockdown of specific genes in PTECs, and provides a potential therapeutic strategy for treating various kidney diseases.